Prevalence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Antibodies in the Mozambican Population: A Cross-Sectional Serologic Study in 3 Cities, July–August 2020 . (24th June 2022) - Arnaldo, Paulo; Mabunda, Nédio; Young, Peter Wesley; Tran, Tiffany; Sitoe, Nádia; Chelene, Imelda; Nhanombe, Armando; Ismael, Nália; Júnior, António; Cubula, Basílio; Inlamea, Osvaldo Frederico; Gudo, Eduardo; et al.
Abstract: Background: The extent of population exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was uncertain in many African countries during the onset of the pandemic. Methods: We conducted a cross-sectional study and randomly selected and surveyed general population and occupational groups from 6 July to 24 August 2020, in 3 cities in Mozambique. Anti–SARS-CoV-2–specific immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies were measured using a point-of-care rapid test. The prevalence was weighted for population (by age, sex, and city) and adjusted for test sensitivity and specificity. Results: A total of 21 183 participants, including 11 143 from the general population and 10 040 from occupational groups, were included across all 3 cities. General population seropositivity (IgM or IgG) prevalence was 3.0% (95% confidence interval [CI], 1.0%–6.6%) in Pemba, 2.1% (95% CI, 1.2%–3.3%) in Maputo City, and 0.9% (95% CI, .1%–1.9%) in Quelimane. The prevalence in occupational groups ranged from 2.8% (95% CI, 1.3%–5.2%) to 5.9% (95% CI, 4.3%–8.0%) in Pemba, 0.3% (95% CI, .0%–2.2%) to 4.0% (95% CI, 2.6%–5.7%) in Maputo City, and 0.0% (95% CI, .0%–.7%) to 6.6% (95% CI, 3.8%–10.5%) in Quelimane, and showed variations between the groups tested. Conclusions: In the first representative COVID-19 serosurveys in Mozambique, in mid-2020, weighted and assay-adjusted seroprevalence in 3 provincial capitals of anti–SARS-CoV-2 ranged from 0.9% to 3.0%, whereas adjusted prevalence in occupational groups ranged from 0.0% to 6.6% with variation between groups. Exposure to SARS-CoV-2 was extensive during the first pandemic wave, and transmission may have been more intense among occupational groups. These data have been of utmost importance to inform public health intervention to control and respond to the pandemic in Mozambique.